Higiena werbalna na portalu Feminoteka.pl - Magdalena Steciąg (Postscriptum Polonistyczne)
The aim of the article is to present a discussion on language on the portal Feminoteka.pl. This nonacademic debate, led by average language speakers, is being analysed through the category of verbal hygiene, which refers to popular, egalitarian and everyday speech. The strategies used by feminists reveal their attempts to transform the style of communication in Poland. They promote discourse of equality, a form of social interaction that uses both argumentation (in a rhetorical sense) and communication practices (in a normative sense) to favour feminist notions.